2015
DOI: 10.3389/fgene.2014.00478
|View full text |Cite
|
Sign up to set email alerts
|

HLA-B allele and haplotype diversity among Thai patients identified by PCR-SSOP: evidence for high risk of drug-induced hypersensitivity

Abstract: Background: There are 3 classes of HLA molecules; HLA class I, II and III, of which different classes have different functions. HLA-B gene which belongs to HLA class I play an important role predicting drug hypersensitivity.Materials and Methods: Nine hundred and eighty-six Thai subjects who registered at a pharmacogenomics laboratory were determined for HLA-B genotype using a two-stage sequence-specific oligonucleotide probe system (PCR-SSOP).Results: In this study, HLA-B alleles did not deviate from Hardy-We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
30
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 31 publications
3
30
1
Order By: Relevance
“…Moreover, there was no significant association between the HLA-B*15:02 with phenytoin-related SCAR irrespective of cutaneous adverse reaction phenotypes ( Table 2). In addition, the frequency of the HLA-B*15:02 in the phenytoin-tolerant controls (14.13%) in this study was comparable with those previously reported in the general Thai population (16.33-16.75%) [26,27]. Consistent with those observed when compared with the phenytoin-tolerant controls, there also was no significant association between the HLA-B*15:02 with phenytoin-related SJS/TEN compared with the general Thai population (Table 3).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Moreover, there was no significant association between the HLA-B*15:02 with phenytoin-related SCAR irrespective of cutaneous adverse reaction phenotypes ( Table 2). In addition, the frequency of the HLA-B*15:02 in the phenytoin-tolerant controls (14.13%) in this study was comparable with those previously reported in the general Thai population (16.33-16.75%) [26,27]. Consistent with those observed when compared with the phenytoin-tolerant controls, there also was no significant association between the HLA-B*15:02 with phenytoin-related SJS/TEN compared with the general Thai population (Table 3).…”
Section: Discussionsupporting
confidence: 91%
“…It is necessary to point out here that the PCR-sequencespecific oligonucleotide probes technique that was used for HLA genotyping in the present study as well as in the previous study was reported by Puangpetch et al [27]. Ambiguous results for HLA-B*56:02 or HLA-B*56:04 genotypes may occur when using this HLA genotyping technique.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…For the alleles with significant associations-and for other alleles in this study-there is a low frequency of polymorphisms within the Thai population: for example, HLA B*51 is predominantly HLA B*51:01 and HLA B*46 is commonly HLA B*46:01. 24 The latter is part of a common Thai haplotype consisting of A*02:07-Cw*01-B*46:01-DRB1*09-DQB1*03:03. It is, therefore, unlikely that higher resolution typing to detect these infrequent polymorphisms with the sample size in this study would significantly confound these results, but additional studies with highresolution typing should be pursued.…”
mentioning
confidence: 99%